Implementasi Digitalisasi Sistem Informasi Akuntansi Berbasis PSAK 14 Persediaan dalam Meningkatkan Efektivitas Operasional Perusahaan Distribusi Fastener PT Multi Teknik Indonesia - Viona Febriana; Alfitri Yani; Rimi Gusliana Mais (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the implementation of digitalization of accounting information systems based on PSAK 202 Inventory in improving operational effectiveness at PT Multi Teknik Indonesia, a fastener distribution company. The objective of this research is to analyze how the implementation of an integrated digital accounting information system influences inventory management and operational efficiency. This study uses a qualitative descriptive approach with data collected through observation, interviews, and documentation. The results show that the implementation of a digital accounting information system integrated with inventory management software and barcode technology significantly improves the accuracy, speed, and reliability of inventory recording. The system enables real-time monitoring of stock levels and automatically records inventory transactions, reducing human errors and delays in reporting. Furthermore, the application of PSAK 202 ensures that inventory is measured based on acquisition cost and systematically recorded, improving the transparency and reliability of financial information. The findings also indicate that digitalization enhances coordination among departments, accelerates decision-making processes, and improves customer service quality through accurate stock availability information. However, several challenges were identified, including limited human resource competence, system disruptions, and high implementation costs. Overall, the study concludes that digital transformation of accounting information systems based on PSAK 202 significantly improves operational effectiveness in fastener distribution companies.